2022
DOI: 10.21203/rs.3.rs-1272120/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

FinTech Innovations and Islamic Banking Performance: Post pandemic Challenges and Opportunities

Abstract: Current research aims to investigate the role of financial technology (Fintech) during pandemics on Islamic financial institutions and banks’ performance. The study identified measures of lockdown executed by numerous countries across the world that have also indicated the significance of leveraging technology and establishing a livelier Islamic finance industry. The results and data analysis identified adoption of greater digitalization and incorporation of fintech strengthens the spirit of the industry in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Research indicates that the increased digitalization and fintech adoption by conventional banks can enhance the industry but may also introduce challenges like security risks, particularly in unstable ecosystems such as during a pandemic (Rahman et al, 2022). While some studies suggest that fintech adoption does not directly impact the performance or risk of conventional banks (Harmadi et al, 2022), others propose that traditional banks encounter both challenges and opportunities due to fintech advancements (Li, 2022).…”
Section: Data Security and Privacymentioning
confidence: 99%
“…Research indicates that the increased digitalization and fintech adoption by conventional banks can enhance the industry but may also introduce challenges like security risks, particularly in unstable ecosystems such as during a pandemic (Rahman et al, 2022). While some studies suggest that fintech adoption does not directly impact the performance or risk of conventional banks (Harmadi et al, 2022), others propose that traditional banks encounter both challenges and opportunities due to fintech advancements (Li, 2022).…”
Section: Data Security and Privacymentioning
confidence: 99%
“…Results and data analysis showed that more digitalization was being adopted, along with a more unstable ecology, threats like pandemics, and new business opportunities. Recent financial years, however, have demonstrated that there is opportunity for expansion and growth, particularly about the issuance of Sukuk in Islamic financial institutions, because of rules and regulations, ease of implementation, and speed of implementation (Rahman et al, 2022). Interestingly, few researchers also discovered that financial digitization is negatively associated with the performance of banks using panel data of China's bank industry from 2013 to 2019.…”
Section: Literature Review and Analysis Of Related Workmentioning
confidence: 99%
“…Meanwhile, the fragility of cyber security, weak regulatory of Fintech, high competition of Fintech companies, customer trust, decrease in market share and increase in customer churn rate are the fundamental challenges of Fintech adaption (Saba, Kouser & Chaudhry, 2019). These statements supported by Ebrahim, Kumaraswamy & Abdulla,(2020); Rahman, Rahiman, Meero & Amin, (2022)where the studies figured out the responsiveness of financial institutions towards new adaptation of Fintech advancement, cyber-attack problem, Fintech regulation, maintaining the talented staffs and unskilled staffs are among the challenges encountered by financial institutions. In the meantime, the regulatory environment and regulation of Fintech are the critical challenges faced in the industry and therefore, review, innovate and enact the new existing regulatory framework to ensure the modern technology is compatible with the transactions including its transparency and disclosure (Islamic Financial Services Board, 2017).Besides that, according to Yateem, (2019), the Islamic financial industry encountered some challenges in adopting Fintech such as unsophisticated staffs and clients, financial risks on a huge amount of transaction, highly competitive with Fintech companies, breach of data privacy that led to the cybercriminal, and uncontrollable regulation if it is beyond the regulatory boundaries in the event money laundering.…”
Section: Challenges Of Fintech Application In Islamic Financial Industrymentioning
confidence: 99%
“…Poor business model framework and undiversified Fintech asset management will cause a decrease in the involvement of investors, customers' difficulty to access the financing option, complexity in the operating process, and length of financing disbursement. The past studies also emphasized that business model and business management strategic planning are significantly related to the challenges of Fintech application in the industry (Hwang et al, 2022;Kijkasiwat, 2021;Rahman et al, 2022).…”
Section: Islamic Financial Business Model and Managementmentioning
confidence: 99%